Significant Wave Height Model Calibration in The Sea Around Banyuwangi and Bali - I.D. Bagus JBS; A.A.N. Satria Damarnegara; Ali Dastgheib; Johan Reyns (Journal of Civil Engineering, 2024)
This paper describes significant wave height downscaling model in south sea around Banyuwangi and Bali. It utilizes 3rd Generation Simulating Wave Nearshore (SWAN) spectral model forced by ERA-5 Reanalysis data of wind and wave. The downscale is done using refined grid in Kuta Beach and Nusa Dua Beach. Model calibration conducted in the offshore and nearshore areas. The offshore wave results are validated using altimeter data, while the nearshore wave results are compared with site measurement in Kuta Beach and Nusa Dua Beach. A parametric study is performed to obtain model sensitivity and compared with observation, such as: wind multiplier factor, bottom friction coefficient, whitecapping, and wave breaking parameter. The model result gives good agreement with altimeter data. Indeed, the wind multiplier factor can be used as one calibration parameter in the wave model. The comparison with measured data shows good agreement in Kuta Beach, where the model can predict the nearshore wave transformation from offshore. Although, in Nusa Dua Beach the model nearshore wave transformation shows more dissipation if compared with wave measurement. Indeed, the downscaling process shows it can be used further in wave climate prediction after calibrated with measurement.